Computerized assessment of social approach behavior in mouse - Page, Damon T.; Kuti, Orsolya J.; Sur, Mriganka (Frontiers in Behavioral Neuroscience, 2009)
Altered sociability is a core feature of a variety of human neurological disorders, including autism. Social behaviors may be tested in animal models, such as mice, to study the biological bases of sociability and how this is altered in neurodevelopmental disorders. An easily quantifiable social behavior frequently used to assess sociability in the mouse is the tendency to approach and interact with an unfamiliar mouse. Here we present a novel computer-assisted method for scoring social approach behavior in mice using a three-chambered apparatus. We find consistent results between data scored using the computer assisted method and a human observer, making computerized assessment a reliable, low cost, high-throughput method for testing sociability.